The liquid phase exfoliation of transition metal oxides for high energy metal oxides for high energy Li-ion batteries - O'Brien, Seán (Trinity College (Dublin, Ireland). School of Chemistry, 2017)
Compared to other electrochemical energy sources, lithium ion (Li-ion) batteries represent the choice energy storage device for small hand held electronics such as power tools or cellphones. This is due mainly to the balance of high energy and power densities present in the devices. It is envisioned that such devices will become major components in the next generation of hybrid electric vehicles (HEV) which may be key in exploitation of alternative energy sources. However, improvements in both the power densities and cycling properties are necessary if applications in HEVs are ever to be realized. Much research has been done on improving these properties with the introduction of nanostructured materials, providing an increase in the overall active surface areas. Recently, two dimensional nanomaterials have shown huge promise in high powered, reusable energy storage devices such as rechargeable batteries and supercapacitors. Specifically, two dimensional transition metal oxide (TMO) materials have shown impressive pseudocapacitive behaviour rivalling that of traditional rechargeable battery systems e.g. LiCoO2 or graphite. This dissertation focuses on some of the important issues surrounding the facile synthesis of TMO nanomaterials, the subsequent fabrication of high energy elec trodes and their electrochemical characterization. A major challenge is to find a facile method to produce a stable, concentrated nanoparticle colloid which can be efficiently used in electrode fabrication ...
Keywords: Chemistry, Ph.D.; PhD Trinity College Dublin, 2017